Psychometric performance of the Arabic versions of the Functional Assessment of Cancer Therapy-Breast plus Arm morbidity (FACT-B + 4) in patients with breast cancer related lymphedema: cross-sectional study - Hind Abdulaziz Al-Hoqail; Mohammed T. A. Omar; Maha Mohammed Al-Marwani; Einas Soliman Al-Eisa (BMC, 2022)
Abstract Background Burden of breast cancer it continues to increase largely because of the aging and growth of the world population and assessment of quality of life is an important outcome measure to facilitate and improved care among breast cancer survivors, the aim of this study was to evaluate evidence of reliability, validity, and responsiveness of the Arabic version of the FACT-B + 4 questionnaire among participants with breast cancer related lymphedema (BCRL) in Saudi Arabia. Methods A prospective cross-sectional study, 51 participants with BCRL completed the Arabic version of FACT-B + 4. Internal consistency and test-retest-reliability were assessed using Cronbach's alpha, intraclass correlation-coefficient (ICC), and limits of agreement according to the Bland Altman method, respectively. The validation studies were carried-out by examining predefined hypotheses (n = 14) for both construct and Known-groups validity. To investigate the responsiveness, the Arabic version of FACT-B + 4 questionnaire was administrated preoperative and 4 weeks postoperatively among the participants with breast cancer (n = 34). Results The Cronbach alpha of the Arabic FACT-B + 4 total score was 0.90 and for the different subscales ranged from 0.74 to 0.89. Test-retest reliability for FACT-B + 4 total score and different subscales was found to be moderate to very strong (ICC 0.51-0.94). The Bland-Altman plot was adequate − 19.24 and 22.10 points. Measurement variability was acceptable for Arabic FACT-B + 4 and ARM subscale (standard error of measurement = 5.34, and 1.34). Moderate correlations (r = 0.42-0.62) were found between the subscale of the FACTB + 4 and the corresponding domains of SF-36. For known group validity, 72% (10 of 14) hypotheses on known group validity were accepted. Conclusion FACT-B + 4 has adequate psychometric properties, thus making it useful for assessing QOL quality of life in Arabic speaking women with BCRL.